Clinical, clinicopathological and diagnostic imaging findings in 14 dogs with suspected fibrocartilaginous embolic myelopathy - POLIZOPOULOU (Ζ.Σ. ΠΟΛΥΖΟΠΟΥΛΟΥ), Z. S.; KARNEZI (Δ. ΚΑΡΝΕΖΗ), D.; KARNEZI (ΚΑΡΝΕΖΗ Γ.), G. (Journal of the Hellenic Veterinary Medical Society, 2017)
Fibrocartilaginous embolic myelopathy was diagnosed in 14 dogs with acute neurological dysfunction, based on history, findings of clinical examination, diagnostic imaging evaluation, follow-up and outcome. The dogs were presented with signs of variable involvement of the spinal cord, which were lateralized in 4 cases. The initial clinicopathological evaluation was unremarkable, while cerebrospinal fluid analysis was abnormal in one dog. Diagnostic imaging investigation (plain radiographs of the spinal column and myelography) did not reveal any abnormalities in the vertebrae and adjacent tissues or compression of the spinal cord, with the exception of one case, where there was evidence of focal intramedullary oedema corresponding to the lesion location. Seven dogs improved significantly with supportive treatment; complete remission of clinical signs was evident in two. Moderate improvement was seen in three animals and minimal or no improvement in four dogs, which were euthanised due to persisting neurological incapacitation.